Zakat administration, distribution and economic growth : a study in the Federal Territory of Malaysia - Densumite, Sorfina; Yusoff, Mohammed (LAP LAMBERT Academic Publishing, 2013)
Islam is a religion built upon five pillars, namely the testimony that there is no god except Allah and Muhammad is the messenger of Allah, establishing prayers, paying zakat, fasting in the month of Ramadhan, and performing pilgrimage in Mecca. Every Muslim must establish himself upon these five pillars. Zakat is one of the five pillars of Islam which is based on the al-Quran and Sunnah (the practices of Allah’s Messenger). Hence, it is obligatory for a Muslim, whose wealth exceeds a specific amount called nisab, to pay zakat in order to fulfil his duty as well as to purify his soul and wealth. The zakat fund is distributed to specific groups of people as stated in the al-Quran. The rational of the imposition of zakat is to prevent the concentration of wealth in a few hands, which is clearly stated in the al-Quran. It plays an essential role an in Islamic social welfare system to alleviate poverty of Muslim communities. Zakat is a major source of revenues in an Islamic economy, and therefore Muslims should understand about the zakat management, particularly on the collection, distribution as well as the effects of zakat distribution on the economy. The literature on concept of zakat is voluminous but empirical works on the practices of zakat of Muslim countries are scanty. Most of the previous studies on zakat distribution and its impact on poverty alleviation is at micro level. There has been very little empirical studies at macro level. The main focus of this book is to examine the zakat administration in the Federal Territory of Malaysia with emphasis on the management of zakat collection and distribution. The book also examines the factors that influence the participation of the zakat payers, zakat contribution, the principle and criteria of zakat collection and distribution, and suggests on how to improve the zakat administration system. In addition, the book also empirically analyses the effects of zakat distribution on economic growth in the Federal Territory of Malaysia.